Analysis of the potential ferroptosis mechanism and multitemporal expression change of central ferroptosis-related genes in cardiac ischemia–reperfusion injury - Wang, Zuoxiang; He, Zhisong; Xuan, Qinkao; Zhang, Yue; Xu, Jialiang; Lin, Jia; Li, Hongxia; Chen, Weixiang; Jiang, Tingbo (Frontiers in Physiology, 2022)
Acute myocardial infraction (AMI) is the most severe type of coronary artery diseases and remains substantial burden to the health-care system globally. Although myocardial reperfusion is critical for ischemic cardiac tissues survival, the reperfusion itself could causes paradoxical injury. Above paradoxical phenomena were known as Ischemia/reperfusion injury (IRI), and the exact molecular mechanism of IRI is still far from elucidated and exist controversy. Meanwhile, ferroptosis is a non-apoptotic form of cell death that has been reported to be associated with various cardiovascular diseases. Thus, we explored the potential ferroptosis mechanism and target in cardiac IRI via bioinformatics analysis and experiment. GSE4105 were obtained from GEO database, consist of rats I/R model and control. After identifying DEFRGs and hub genes of cardiac IRI, we performed enrichment analysis, co-expression analysis, drug-gene interaction prediction and mRNA-miRNA regulatory network construction. Moreover, we validated and explored multitemporal expression of hub genes in an H/R-induced H9C2 cell injury model under different condition via RT-qPCR. A total of 43 DEFRGs and 7 hub genes (Tp53, Tnf, Hif1a, Il6, Hmox1, Xbp1 and Casp8) were screened based on bioinformatics analysis, and the functional annotation of these genes revealed apoptosis and the related signaling pathways could have association with the pathogenesis of ferroptosis in cardiac IRI. In addition, the expression of 7 hub genes in IRI models were found higher than control under different hypoxia/reoxygenation condition and time point. In conclusion, the analysis of 43 DEFRGs and 7 hub genes could reveal the potential biological pathway and mechanism of ferroptosis in cardiac IRI. In addition, the multitemporal expression change of hub genes in in H9C2 cells under different hypoxia/reoxygenation condition could provide clues for further ferroptosis mechanism exploring, and 7 hub genes could be potential biomarkers or therapeutic targets in cardiac IRI.